2019
DOI: 10.1523/jneurosci.3163-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Membrane Potential Fluctuations Evince Network Scale-Freeness and Quasicriticality

Abstract: What information single neurons receive about general neural circuit activity is a fundamental question for neuroscience. Somatic membrane potential (V m ) fluctuations are driven by the convergence of synaptic inputs from a diverse cross-section of upstream neurons. Furthermore, neural activity is often scale-free, implying that some measurements should be the same, whether taken at large or small scales. Together, convergence and scale-freeness support the hypothesis that single V m recordings carry useful i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 153 publications
1
11
0
Order By: Relevance
“…In addition, assuming that fluctuations of the early SEP reflect changes in EPSCs which in turn depend on pre-stimulus membrane potentials, it follows that these dynamics may be manifested in ongoing modulations of membrane potentials. Intriguingly, dynamics close to criticality have been demonstrated for membrane potential fluctuations in pyramidal neurons of the visual cortices in turtles (Johnson et al, 2019), consistent with our idea of the origin of power-law dynamics in early human SEPs.…”
Section: Neurophysiological Basis Of Temporal Fluctuations In the Earsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, assuming that fluctuations of the early SEP reflect changes in EPSCs which in turn depend on pre-stimulus membrane potentials, it follows that these dynamics may be manifested in ongoing modulations of membrane potentials. Intriguingly, dynamics close to criticality have been demonstrated for membrane potential fluctuations in pyramidal neurons of the visual cortices in turtles (Johnson et al, 2019), consistent with our idea of the origin of power-law dynamics in early human SEPs.…”
Section: Neurophysiological Basis Of Temporal Fluctuations In the Earsupporting
confidence: 88%
“…Furthermore, when focusing on the temporal domain, power-law dynamics can be found in human resting-state fMRI networks (Tagliazucchi et al, 2013), as well as in amplitude fluctuations of alpha band activity in the MEG (Linkenkaer-Hansen, Nikouline, Palva, & Ilmoniemi, 2001;Palva et al, 2013). In addition, a recent study observed that even single-cell membrane potentials in the turtle visual cortex show critical dynamics (Johnson, Wright, Xia, & Wessel, 2019). These findings suggest that fluctuations of the instantaneous brain state are characterized by a complex spatio-temporal structure, leading to endogenous dynamics in cortical excitability which, in turn, should affect the commonly observed variability in brain responses, such as ERPs.…”
mentioning
confidence: 99%
“…Moreover, it was observed that stimuli during a Downstate could often evoke disproportionately large responses, by inducing transitions to an Upstate. More recent studies suggest such effects to be inducible because the neocortex is a system with criticality phenomena, where small changes at critical states can cause avalanche effects of increased excitability that spread widely through the cortical network (Wright and Wessel, 2017 ; Johnson et al, 2019 ). Although our data indicate a much more fine-grained subdivision of cortical states than the binary dichotomy between Up and Down states, such avalanche effects could be the underlying reason for the response types we observed here.…”
Section: Discussionmentioning
confidence: 99%
“…The latter can be employed to capture the non-Euclidean geometry of the human brain and its relation with developmental traits and multi-scale dynamics (Werner, 2010 ; Hofman, 2014 ). Fractality and multi-scale organization are indeed inherent properties of cortical circuits and are closely related to the concept of criticality (Poil et al, 2008 ; Friedman et al, 2012 ; Haimovici et al, 2013 ; Massobrio et al, 2015 ; Marshall et al, 2016 ; Johnson et al, 2019 ), in which a neuronal circuit operates at the boundary between an ordered, strongly coupled state and a disordered, weakly coupled one. Neuronal systems at criticality exhibit long-range spatial and temporal correlations with power-law distributed statistics, facilitating a broad dynamic repertoire and swift communication among distant areas.…”
Section: Discussionmentioning
confidence: 99%